2022
DOI: 10.3389/fcvm.2022.831390
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Methods for Predicting Long-Term Mortality in Patients After Cardiac Surgery

Abstract: Objective:This study aims to construct and validate several machine learning (ML) algorithms to predict long-term mortality and identify risk factors in unselected patients post-cardiac surgery.MethodsThe Medical Information Mart for Intensive Care (MIMIC-III) database was used to perform a retrospective administrative database study. Candidate predictors consisted of the demographics, comorbidity, vital signs, laboratory test results, scoring systems, and treatment information on the first day of ICU admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Areas where RL has been applied, that are relevant for cardiovascular monitoring include targeting of measurements during monitoring and choosing, timing and dosing of treatment steps. Many diagnostic and prognostic tasks in the healthcare domain are facilitated through the use of a variety of supervised ML models including logistic regression (LR), support vector machines (SVM), and ensemble methods such as random forest (RAF) and extra trees (39)(40)(41)(42). This group of AI algorithms are often applied on time-independent tabular patient information.…”
Section: Common Ai Methods Applied To Clinical Data For Patient Monit...mentioning
confidence: 99%
“…Areas where RL has been applied, that are relevant for cardiovascular monitoring include targeting of measurements during monitoring and choosing, timing and dosing of treatment steps. Many diagnostic and prognostic tasks in the healthcare domain are facilitated through the use of a variety of supervised ML models including logistic regression (LR), support vector machines (SVM), and ensemble methods such as random forest (RAF) and extra trees (39)(40)(41)(42). This group of AI algorithms are often applied on time-independent tabular patient information.…”
Section: Common Ai Methods Applied To Clinical Data For Patient Monit...mentioning
confidence: 99%
“…Like our study, a recent survey reported the 25 important predictors selected by the RF algorithm for mortality after cardiac surgery, which include chronic HF, mechanical ventilation, sodium, blood pressure, Hb, age, creatinine, renal failure, dyslipidemia, and glucose. 10 In another study, XGB selected the serum creatinine, weight, age, and EF as the most important predictor for in-hospital and 30-day mortality of cardiac surgery. 69 Besides, age, renal disease, chronic heart failure, and hyperlipidemia were selected as influential factors of long-term survival in elderly patients with CABG by various ML algorithms.…”
Section: T a B L E 1 Evaluation Of Ml Models For The Prediction Of 1-...mentioning
confidence: 99%
“…In this study, LR was found to be the second best-performing ML model with a slight difference in accuracy from the Ada (AUC = 0.797). 10 As LR is sometimes considered a traditional model and not an ML algorithm, a meta-analysis concluded that ML was superior to the LR model in terms of mortality prediction after cardiac surgery, with a nonsignificant trend toward the better predictive ability of each ML algorithm. Nevertheless, the clinical importance of such an enhancement remains challenging.…”
Section: T a B L E 1 Evaluation Of Ml Models For The Prediction Of 1-...mentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of ML models, supplementing various societal risk models, for predicting outcomes in other types of surgeries like aortic valve replacement has been demonstrated by Kilic et al [5]. In fact, ML models have even been used for predicting long-term mortality following cardiac surgery [6].…”
mentioning
confidence: 99%